Enhancing Stoichiometry Problem-Solving Skills through 5E Inquiry-Based Learning Combined with the FOPS Strategy - Kamolsiri Sudchanham; Kanyarat Cojorn (Universitas Negeri Malang, 2025)
This classroom action research aimed to improve the chemistry problem-solving abilities of Grade 10 students using the 5E Inquiry-Based Learning model combined with the FOPS Strategy, with the goal of achieving a 70 percent success criterion. The target group consisted of 25 Grade 10 students from Sarakhampittayakhom School, Thailand. The research instruments included (1) lesson plans incorporating the 5E Inquiry-Based Learning model and the FOPS Strategy, (2) a chemistry problem-solving ability test, (3) a behavioral observation checklist for assessing problem-solving abilities, and (4) student interviews. Quantitative data were analyzed using statistics such as mean, percentage, and standard deviation, while qualitative data were analyzed using content analysis. The results showed that in the first cycle, 10 students (40.00 percent) achieved the 70 percent criterion. In the second cycle, the number increased to 17 students (68.00 percent). By the third cycle, 23 students (92.00 percent) met the criterion, demonstrating significant improvement in problem-solving abilities.